Theory of Planned Behavior and Social Entrepreneurial Intentions in the Badulla District in Sri Lanka: A Moderation Analysis - Sanmugam, Siromiya (Journal of Emerging Management Studies, 2025)
Purpose - The social enterprise is a process of forming value by utilizing resources in new ways to explore new opportunities for society. The current study adopted the Theory of Planned Behavior (TPB). The theory demonstrates that a person’s intention to perform a behavior is shaped by their attitudes, subjective norms, and perceived behavioral control. In addition to that, this research evaluates the impact of TPB on social entrepreneurial intention (SEI), focusing on social support as a moderator among selected aspiring social entrepreneurs in the Badulla district. Design/methodology/approach – A quantitative research design was adopted, and the purposive sampling technique was utilized to select the sample of 105 social entrepreneurs from an unknown population. The structured questionnaire was distributed as a Google Form via email to the respondents. The gathered data were subjected to descriptive, regression, and hierarchical regression analysis in SPSS. Findings and Conclusion - According to the results, all the independent variables – entrepreneurial attitude, subjective norms, and perceived behavior control – have a positive impact on social entrepreneurial intention. However, in the context of the moderating effect of social support, it partially moderates these relationships. It positively moderates only the effect of perceived behavioral control on SEI but does not moderate entrepreneurial attitude and subjective norms. As a conclusion, TPB effectively decides social entrepreneurial intention in this context. Therefore, social support did not directly strengthen these relationships. Originality/value – The study contributes by extending TPB with social support in Sri Lankan culture. It provides fresh insights into how family and friends shape entrepreneurial behavior and presents the significance of collaborative impacts in fostering entrepreneurship.